The recording and characteristics of pulmonary rehabilitation in patients with COPD using The Health Information Network (THIN) primary care database - Hakamy, Ali; McKeever, Tricia M.; Gibson, Jack E.; Bolton, Charlotte E. (Nature Publishing Group, 2017)
Pulmonary rehabilitation is recommended for patients with COPD to improve physical function, breathlessness and quality of life. Using The Health Information Network (THIN) primary care database in UK, we compared the demographic and clinical parameters of patients with COPD in relation to coding of pulmonary rehabilitation, and to investigate whether there is a survival benefit from pulmonary rehabilitation. We identified patients with COPD, diagnosed from 2004 and extracted information on demographics, pulmonary rehabilitation and clinical parameters using the relevant Read codes. Thirty six thousand one hundred and eighty nine patients diagnosed with COPD were included with a mean (SD) age of 67 (11) years, 53% were male and only 9.8% had a code related to either being assessed, referred, or completing pulmonary rehabilitation ever. Younger age at diagnosis, better socioeconomic status, worse dyspnoea score, current smoking, and higher comorbidities level are more likely to have a record of pulmonary rehabilitation. Of those with a recorded MRC of 3 or worse, only 2057 (21%) had a code of pulmonary rehabilitation. Survival analysis revealed that patients with coding for pulmonary rehabilitation were 22% (95% CI 0.69–0.88) less likely to die than those who had no coding. In UK THIN records, a substantial proportion of eligible patients with COPD have not had a coded pulmonary rehabilitation record. Survival was improved in those with PR record but coding for other COPD treatments were also better in this group. GP practices need to improve the coding for PR to highlight any unmet need locally.